1987
DOI: 10.1042/bj2480259
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular structure of tripeptidyl peptidase II from human erythrocytes as studied by electron microscopy, and its correlation to enzyme activity

Abstract: Tripeptidyl peptidase II is an extralysosomal serine peptidase of an unusually large size, i.e. Mr greater than 10(6) for the native enzyme and Mr 135000 for the subunit. The enzyme from human erythrocytes was studied by electron microscopy on samples negatively stained by ammonium molybdate. Two different structural representations of the purified enzyme were obtained, both with a length of about 50 nm, and consisting of repetitive substructures. Upon dialysis of the enzyme against a Tris/HCl buffer, the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…7B). TPP II is a multimeric protease complex that may require proper assembly for normal function (26,48). Superose 6 gel filtration chromatography revealed that the increase in AAF-AMC hydrolyzing activity detected under these conditions of TPP II vac infection corresponded to a single peak eluting just before the 26S proteasome (Figs.…”
Section: Overexpression Of Tpp IImentioning
confidence: 97%
“…7B). TPP II is a multimeric protease complex that may require proper assembly for normal function (26,48). Superose 6 gel filtration chromatography revealed that the increase in AAF-AMC hydrolyzing activity detected under these conditions of TPP II vac infection corresponded to a single peak eluting just before the 26S proteasome (Figs.…”
Section: Overexpression Of Tpp IImentioning
confidence: 97%
“…thimet oligopeptidase, prolyl oligopeptidase, aminopeptidases, or insulin-degrading enzyme) as determined with specific fluorogenic substrates or by immunoblotting. However, this step did remove the very high molecular weight enzyme, TPP-II (34,35). This enzyme has been proposed to play a role in final steps of intracellular protein degradation by degrading peptides generated by proteasomes (36).…”
Section: Antigenic Peptides Are Rapidly Digested By Cytosolicmentioning
confidence: 99%
“…In the latter case, the activity dropped to about one-tenth and recovered to some extent upon partial reassembly. This hinted at a correlation between oligomeric state and specific activity and elicited speculations on a regulation of the enzyme activity via association/dissociation (2,29,30).…”
mentioning
confidence: 98%
“…The TPP II holo-complex has been reported to decay under conditions such as dialysis (29) or freezing/thawing (30), with a concomitant decrease of activity. In the latter case, the activity dropped to about one-tenth and recovered to some extent upon partial reassembly.…”
mentioning
confidence: 99%